Classifications of classical Malay aristocratic architecture:identifying generic and variant forms - Raja Abdul Kadir, Tengku Anis Qarihah; Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Kamaruddin, Zumahiran (Malaysian Institute of Planners, 2018)
The paper reports on a basic classification based on formal and morphological similarities of large vernacular buildings across the Malay region, based on their frontages; with the aim of developing a universal regional language and set of rules of local architecture for urban and multi-storeys typologies. Generally, seen as idiosyncratic and individualistic, Malay regional palaces and mansions across different states and regions under former Sultanates, exhibit different vocabularies, yet have underlying similarities. While form and architecture may arise from the local technology and construction methods of the era, aesthetic expressions of these palaces recall formal archetypes which can be described, and characterised, regardless of location. Focusing on palaces in Malaysia and East Sumatran region from the late 1800s onwards, recurring forms of a Malay-Classical language are observed and classified into generic morphologies of frontages. The aim is towards formal taxonomy that can represent a more inclusive architectural identity of the region, rather than identities based on nations. By defining the ‘generic’ and the ‘variant’, significant palaces across the Malay region are discussed and positioned within a classification based on a range of generic archetypes. Variants include cases which have absorbed external influences yet retain the essences of local form, while some examples, refer to elements that have modernised been yet represent the last offshoot or branch of the same region. To identify generic rules and frameworks of design, the regional roots of form, including frontages, for public buildings is crucial for urbanscape and the urgency of developing guidelines and a set of compositional rules and language of urban architecture derived from the essences of tradition and past forms.